ANALISIS KEBERPIHAKAN HUKUM TERHADAP HAK ASASI MANTAN NARAPIDANA DALAM PENGANGKATAN NOTARIS BERDASARKAN PASAL 3 HURUF (h) UNDANG-UNDANGNOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - HASANUL JIHADI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Madiasa Ablizar3. Suprayitno Notary is a Public Official as written in the Law of the Republic of Indonesia No. 30/2004 in conjunction with the Law No. 2/2014 on Notary, in Chapter I on General Provisions. This is a normative legal research, which is descriptive analytical, which approach to the problems done by studying the provisions in the prevailing laws and regulations in the field of notarial law, in this case, UUJN (Notarial Act) No. 3/2004 in conjunction with UUJN No. 2/2014. The results of the research finds out that the legal status of the notary candidate who is a former juvenile prisoner, with the provisions in Article 3 letter (h) of UUJN-P No. 2/2014. Article 28 D paragraph (1), (2), (3) and (4) of the Constitution 1945 has firmly secured human rights to have an occupation, to make a living that is decent for the benefit of humanity, as long as the occupation is not contrary to the laws. The validity of the provisions in Article 3 letter (h) of UUJN-P No. 2/2014 can be revoked by performing the rights of Material Test to the Constitutional Court so that the former juvenile prisoner can also be designated as a notary.Keywords: Legal Partiality, Former Juvenile Prisoner and Notary Designation